Niveles de carboxihemoglobina en policías de tránsito de la ciudad de Huancayo, 2019 - Mallqui, Roxana (2020)
The present investigation was carried out with the objective of knowing if the traffic policemen of the city of Huancayo in 2019 exceeded the normal values of carboxyhemoglobin in blood, for which the carboxyhemoglobin COHb) was quantified in the blood of 64 traffic policemen. The study was carried out based on the scientific research method, a type of applied research and a non-experimental-descriptive and cross-sectional research design. The parametric statistical method was also used. The results showed that 40 (62.5%) gave lower than normal COHb values and 24 (37.5%) gave higher than normal COHb values, being that the normal value of carboxyhemoglobin in blood is from 1 to 2 %. The values according to gender were obtained 28.1% in women and 9.4% in men with higher than normal COHb values. Regarding age, it was divided into four groups, finding levels higher than the normal COHb value in children under 25 years 14.1%, from 26 to 30 years 17.2%; in the group between 31 to 40 years 6.3%. ; the results according to the time in the traffic unit were as follows: less than 1 year 6.3%, 1 year 15.6%, 2 years 14.1%, 3 to 5 years 1.6%.